Representasi Penguasa dan Oposisi dalam Cerita Rakyat “Buaya Putih dan Keuyeup Bodas”: Representations of Authority and Opposition in the Folktale "Buaya Putih and Keuyeup Bodas" - Marini Ganthina Putri; Ece Sukmana; Kuswara; Asep Saepurokhman (Deiksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research is motivated by the importance of preserving folktales as a medium for cultural reflection and social critique, particularly in the context of development and power relations. The folktale "Buaya Putih and Keuyeup Bodas" was chosen because it contains ideological and ecological symbols that remain relevant to contemporary socio-political dynamics. This study aims to examine the representation of power and opposition within the story using Propp’s narrative analysis, Barthes’ semiotics, and Hall’s theory of representation. A descriptive method was employed with a phenomenological approach to the text and interviews with local communities. The analysis reveals that the character Buaya Putih represents hegemonic power that is greedy and exploitative, while Keuyeup Bodas symbolizes an oppositional force that upholds ecological harmony and the interests of the people. The tale conveys a critique of development projects, such as the Jatigede Dam, that disregard ecological balance and community participation. Thus, folktales serve not only as entertainment but also as spaces for education and reflection on power practices and social injustice. This study underscores the need for interdisciplinary approaches in uncovering cultural meanings in folklore to ensure their continued relevance and reinterpretation by current generations.